Chemosensory protein 4 is required for Bradysia odoriphaga to be olfactory attracted to sulfur compounds released from Chinese chives - Yang, Yuting; Hua, Dengke; Zhu, Jiaqi; Wang, Fu; Zhang, Youjun (Frontiers in Physiology, 2022)
Bradysia odoriphaga (Diptera: Sciaridae) is a serious pest of Chinese chives in China. By capturing and binding to environmental semiochemicals and by transporting those chemicals to olfactory receptors, chemosensory proteins (CSPs) are important components of insect olfactory systems. However, the mechanism of olfaction in B. odoriphaga and related behavioral processes have not been characterized. Here, we found that BodoCSP4 has an important olfactory function. qRT-PCR indicated that BodoCSP4 expression was highest in the heads (excluding antennae) of male adults and in male antennae. Competitive binding assays with 33 ligands indicated that BodoCSP4 binds well with methyl allyl disulfide, diallyl disulfide, and n-heptadecane; the corresponding dissolution constants (Ki) were as high as 5.71, 5.71, and 6.85, respectively. 3D-structural and molecular docking indicated that BodoCSP4 has five α-helices and surrounds the ligand with certain hydrophobic residues including Leu60, Leu63, Leu64, Ala67, Val28, Ile30, Ile33, Leu34, and Val86, indicating that these residues help BodoCSP4 bind to ligands. Silencing of BodoCSP4 significantly decreased the attraction of B. odoriphaga males to diallyl disulfide and n-heptadecane but not to methyl allyl disulfide in Y-tube olfaction assays. These results increase our understanding of how BodoCSP4 contributes to host and female location by B. odoriphaga males.